Sharia Life Insurance: Legal Basis and Operational Systems - Munawir Idris; Darminto Hartono Paulus (Jurnal Hukum Prasada, 2020)
Islamic life insurance is a non-bank financial institution that is used by the Muslim community as a medium in anticipating risks that might arise in the future. So that people make insurance, especially sharia life insurance as an alternative in dealing with future risks related to one's life. This study aims to determine the legal basis for sharia life insurance and its operating system as a forum for information for Muslim communities in Indonesia. In this study, the author uses the doctrinal research method in which the approach used is the regulatory approach (Islamic law) and the conceptual approach. This research prioritizes secondary data in its management such as primary legal materials, secondary legal materials, and tertiary legal materials. This study shows the origin of Islamic insurance is derived from the traditions of the Arab community at the time of the Prophet Muhammad, called Akilah. If someone dies (killed) by someone, then the family of the murderer is obliged to pay blood money (diyat) to the heirs of the victim. The blood money was collected from murderous families and then handed over to the heirs of the victims. This tradition later developed into Islamic insurance known today. Sharia insurance operational system is to use two contracts, namely Tabarru contract and mudharabah contract. With the existence of these two contracts, the elements of gharar, maysir and riba can be removed.